2008
DOI: 10.1007/s00330-008-1032-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of sonoelastography in non-palpable breast lesions

Abstract: The purpose of this study was to evaluate the diagnostic utility of sonoelastography in differentiating benign from malignant non-palpable breast lesions. A total of 293 BI-RADS 3-5 (Breast Imaging Reporting And Data System) impalpable breast lesions in 278 women was evaluated with B-mode ultrasound (US) and subsequently with sonoelastography (SE) before performing US-guided biopsy. Among the 293 lesions (size up to 2 cm), 110 (37.5%) were histologically malignant and 183 (62.5%) benign. Lesions that were mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
3
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 16 publications
5
94
3
9
Order By: Relevance
“…In addition, the role of elastography is limited in very dense fibrous parenchyma, in presence of hematoma and breast implants. Some studies have also showed its value in the differentiation of benign and malignant lymph nodes (18). It is reported that both the mechanical type of elastography method that we used in this study and the shearwave elastography method that is more software dependent provide similar results (19).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, the role of elastography is limited in very dense fibrous parenchyma, in presence of hematoma and breast implants. Some studies have also showed its value in the differentiation of benign and malignant lymph nodes (18). It is reported that both the mechanical type of elastography method that we used in this study and the shearwave elastography method that is more software dependent provide similar results (19).…”
Section: Discussionmentioning
confidence: 60%
“…It is stated that elastography can be clinically used as an imaging method in patient follow-up or as a method for determining whether to perform an invasive procedure or not. It has been reported that distinguishing between score 2 and score 3 lesions by elastography might be difficult in some cases, but diagnosing score 1 lesions is very easy since a blue color is not present in these lesions (18). According to our study, it is unlikely to have trouble in the elastographic diagnosis of cystic lesions, however it is obvious that problems will arise due to the nature of some benign lesions mainly composed of fibrous tissue such as stromal fibrosis and sclerosing adenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, benign lesions are white and malignant lesions are dark, while cysts show a bull's eye appearance with a white center and a surrounding dark halo. In color images, the lesions present characteristics which have been assigned a score from 1 to 5 (similar to the BI-RADS classification), where benign or probably benign lesions (more elastic) are green with possible blue points, whereas malignant lesions (less elastic) are almost entirely blue with a possible halo which can be correlated with a desmoplastic reaction in the surrounding tissues [22,23]. Typically, simple and complicated cystic lesions present a triphasic pattern with a blue, more rigid layer at the surface, an intermediate green layer and a deep layer which is red.…”
Section: Us Parameters In the Diagnosis Of A Probably Benign Lesionmentioning
confidence: 99%
“…Writers found 86.5 % sensibilities, 89.9 % specificity, and 88.3 % diagnostic correctness. Scaperrotta et al applied more basic three-pointed systems developed on the basis of classification system used by Itoh et al, and they obtained 80 % sensibility and 80.9 % specificity levels similar to US study [11]. As a main limitation of elastography, writers determined that it was executive dependent and due to this it varied from.…”
Section: Discussionmentioning
confidence: 88%
“…For this evaluation, a software is used in which soft lesions seem to be bright, hard lesions seem to be dark and malignant lesions are more specific than benign lesions. On the other hand tissues seem to be in different color spectrum according to their hardness [6][7][8][9][10][11]. Yet, there is no agreement on the method or classification which has the most clinical applicability.…”
Section: Introductionmentioning
confidence: 99%